Adsorpsi Zat Warna Rhodamin B Menggunakan Abu Terbang (Fly Ash) Batubara Teraktivasi Dengan Variasi Massa Adsorben Dan Suhu Adsorpsi - Riris Verawati; Rozanna Sri Irianty; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The increasing use of dyes in various industries causes environmental problems that must be addressed. Various methods have been done to reduce the dye waste, one of which is adsorption. Using of inexpensive and easily obtained adsorbents is one of the considerations in choosing the type of adsorbent used. The purpose of this research was to determine the ability of activated fly ash with NaOH by adsorbing Rhodamine B dyes at equilibrium with variations in adsorbent mass and adsorption temperature and determining the adsorption equilibrium model. This research was carried out by varying the mass of the adsorbent and the adsorption temperature. The result showed that the best mass of adsorbent for adsorbing rhodamine B at 140 minutes was 5 grams at an adsorption temperature 55 to obtain 89% of adsorption efectiveness. The adsorption mechanism meets the FreundLich isotherm model with a values of R2 equal to 0,935.   Keywords: adsorption, activation, dye waste, fly ash, rhodamin B